Cerium oxide standing out as an electron transport layer for efficient and stable perovskite solar cells processed at low temperature. Issue 4 (6th January 2017) - Wang, Xin; Deng, Lin-Long; Wang, Lu-Yao; Dai, Si-Min; Xing, Zhou; Zhan, Xin-Xing; Lu, Xu-Zhai; Xie, Su-Yuan; Huang, Rong-Bin; Zheng, Lan-Sun
Abstract : Low-temperature, solution-processed cerium oxide can serve as a promising electron transport layer to replace commonly used TiO2 in planar perovskite solar cells, with high efficiency and enhanced stability. Abstract : In high performance perovskite solar cells (PSCs), the electron transport layer (ETL) has overwhelmingly been dominated by compact titanium oxide (TiO2 ), which typically requires sintering at around 500 °C. Such a high-temperature sintering procedure prevents TiO2 -based PSCs from matching well with plastic substrates and low-cost manufacturing. Here we report cerium oxide (CeO x, x = 1.87), that was prepared facilely through a simple sol–gel method at low temperature (∼150 °C), as an alternative to high-temperature sintering processed TiO2 in the regular architecture of PSCs. With a PCE of 14.32% from the involvement of an optimized CeO x ETL through adjusting the precursor solution, and a higher PCE of 17.04% through introducing a [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) interfacial layer between the CeO x ETL and the perovskite layer, the present work about CeO x -based PSCs renders low-temperature solution-processed CeO x an excellent ETL for high performance perovskite solar cells with improved stability.